Error Analysis of Academic Writing Papers of English Education Students at IAIN Fattahul Muluk Papua - Ukka, Syamsir Bin; Mursyid, Andi Miftahul Maulidil; Wijayanti, Erfin (Universitas Islam Ahmad Dahlan (UIAD), 2021)
This research aims to identify the factors of writing errors and efforts to identify the resolution of errors in writing academic papers for English Education students at IAIN Fattahul Muluk Papua. The theory used to examine the research problem is standard and correct language, grammar theory, and error analysis as the leading theory. The research method is descriptive-qualitative. The results showed that the writing error factor was in morphological errors, lexicon errors, syntactic errors, and systematics of writing. First, morphological errors include punctuation errors, spelling errors, and vocabulary errors. Second, lexicon errors include grammatical errors and conciseness errors. Third, syntactic errors include unclear sentences, sentences that have ambiguous intentions and incomplete sentences. Fourth, systematic errors in writing include the thickness of letters, coherence, the distance between sub-chapters and incompleteness of sentences. Efforts to resolve writing errors, so that its do not happen again by realizing an English version of the academic paper writing module in simple language equipped with systematic explanations, formats, and substance of academic papers.